Pricing of delivered products in associated transactions - Đinh Thị Ngọc Mai (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
In fact, a business's production and trading of products and goods not only carries out independent transactions but also implements related transactions. Determining the price of products and goods upon transfer is called pricing of transferred products. The price of delivered products is also a tool to control costs, profit distribution, efficiency evaluation, etc. Benefits of businesses when determining profits. In this article, the author deals with the application of methods of pricing transfer products, reviewing and analyzing related issues, thereby helping managers to have a complete and comprehensive view. than the impact and thought factors of this price type in associated transactions.